Devolution of HRM practices: perspectives of two major Japanese electrical and electronics companies in Malaysia - Abang Ekhsan, Abang Othman (Faculty of Business and Administration, University of Bucharest, 2008)
This study examines the devolution of HRM functions, the rationale and problems of such devolution to line management in the context of applications and processes in two major Japanese multinational companies in Malaysia. The research used mixed methodology via case studies and questionnaire surveys. Overall 29 questionnaires from two companies were analyzed, a response rate of 58 percent. In addition, the views of the Executive Director, Head of HR, and line managers were sought regarding their role, involvement and problems of devolvement to line managers. Analysis of questionnaire responses and interviews shows that devolution of HRM functions to the line managers was adopted by both organizations, though their approaches varied in terms of process. The study revealed a high degree of devolution of responsibility to line managers for recruitment and selection and training and development. The devolution of training and development functions specifically to a separate department resulted in their increased effectiveness. Extensive participation and a close working relationship on HR-related issues between HR managers and line managers jointly contributed to the effectiveness of the companies’ devolution of HRM functions.